2018
DOI: 10.1590/1806-9061-2017-0676
|View full text |Cite
|
Sign up to set email alerts
|

Digestible Lysine Requirements the Performance, Carcass Traits and Breast Meat Quality of Slow-Growing Broilers

Abstract: Three experiments were conducted to estimate the digestible lysine requirements of slow-growing broilers on their performance, carcass traits, and breast meat quality. Different broilers were evaluated in each experiment. In Experiment 1, broilers were evaluated from 29-49 days of age (grower phase I), in Experiment 2, from 50 to 69 days old (grower phase II), and in Experiment 3, from 70-84 days old (finisher phase). A completely randomized design with five treatments of four replicates each was applied in al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
0
2
0
1
Order By: Relevance
“…Higher body weight gain was found in diet with protein bound Lys (Lys from ingredients) as related to diets with free Lys sources (L-Lys HCl and L-Lys sulfate) supplementation. As, lysine has an important role in broiler growth and a sufficient amount of lysine is required to meet that requirement (Brasil et al, 2018). Results are in line with findings of Oliveira et al (2014) reported that body weight gain was significantly higher in protein bound Lys diets as compared to diets with Lys supplementation.…”
Section: Discussionsupporting
confidence: 85%
“…Higher body weight gain was found in diet with protein bound Lys (Lys from ingredients) as related to diets with free Lys sources (L-Lys HCl and L-Lys sulfate) supplementation. As, lysine has an important role in broiler growth and a sufficient amount of lysine is required to meet that requirement (Brasil et al, 2018). Results are in line with findings of Oliveira et al (2014) reported that body weight gain was significantly higher in protein bound Lys diets as compared to diets with Lys supplementation.…”
Section: Discussionsupporting
confidence: 85%
“…Indeed, Jasek et al (2018) investigated the effect of a multicarbohydrase-containing α-galactosidase and xylanase on the ileal digestible energy, crude protein, and ileal amino acid digestibility of broilers and found that enzyme supplementation improved the digestibility of individual amino acids, including aspartic acid, threonine, serine, glutamic acid, proline, glycine, alanine, cysteine, valine, methionine, isoleucine, leucine, tyrosine, phenylalanine, lysine, histidine, and tryptophan. In this assumption, among these amino acids, lysine stands out because it comprises ~7.5% of all carcass protein (Sklan and Noy, 2004) and, thus, directly influences carcass parameters (Brasil et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Its various parts are used as fodder, herbal medicine, spices, food, natural coagulants, nectar for bees, fuel and fertilizer [12,13]. The dried, ground leaves of M. oleifera are rich in proteins, lipids, fibres, carbohydrates and minerals.…”
Section: Introductionmentioning
confidence: 99%